Application of Simulation of Dining Philosophers Problem in Concurrent Process - Parasian DP Silitonga; Irene Sri Morina; Romanus Damanik (Universitas PGRI Kanjuruhan Malang, 2021)
A classic simulation that can describe concurrent processes on an operating system is the dining philosopher problem. In the dining philosophers problem, there is the possibility of a deadlock, a condition in which two or more processes cannot continue their execution. This research produces a software application that can simulate the concurrent process and prevent deadlock problems that occur. The benefit of the simulation in this study is as a visualization of the completion of dining philosophers problems and as an additional facility in the teaching and learning process, especially in operating system courses